Didactic of the Hadith lesson in e-learning and the quality question; An analytical descriptive study of a case in higher education in Morocco - Abouali, Zineb (Journal of Educational and Psychological Sciences, 2022)
The study aimed at revealing the modern didactical methods, provided by e-learning, through the Digital platform of the University in Casablanca, taking into account the level of educational environment in all its components, to achieve quality in the outputs of Hadith lesson, through e-learning. The researcher used the descriptive approach for the teaching situation of Hadith at Casablanca University, based on the observation of theoretical lessons experience for two semesters across the digital platform, which is used by reference documents on e-learning mentioned in the latest review index. The research came in an introduction to the overall framework on the digital platform, the importance of the subject, objectives and previous studies on the subject, problematic and asking questions, followed to indicate the terms of the study, and then stages of the preparation and achievement of Hadith lesson On the digital platform for its specificities imposed by the quality of the digital education approved, and then the challenges of e-learning and its hats that may hinder the quality aspired by higher education. The study concluded that progress in digital university teaching in the Hadith lesson requires attention to the modern didactical methods, which guarantee the quality of outputs. According to the results, the researcher submitted recommendations: confirmed the importance of using the latest Didactical teaching methods and modern technologies in the Hadith lesson, and to conduct supplementary studies on the subject.
Keywords: Didactic of Hadith Lesson; Electronic Education; Quality of Teaching Hadith in Higher Education